Relevance and quality of the public and municipal services in the Republic of Komi: sociological analysis - Y. M. Bolshakova (Ассоциация независимых экспертов «Центр изучения кризисного общества» (in English: Association for independent experts “Center for Crisis Society Studies”), 2015)
The article analyzes the regional technologies of the provision of public and municipal services, assesses feedback on the effective provision of the public and municipal services. The author argues the necessity of the transparency advance of public authorities and the transition to the social management on the basis of real-life situations.